GOD’S GENDER IN RELIGIONS PERSPECTIVE IN INDONESIA - Siswadi, Gede Agus; Kuswanjono, Arqom; Permatasari, Rr. Yudiswara Ayu (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
The search and discussion of God are never-ending in the study and history of human civilization. Humans always want to prove the existence of God through arguments from thoughts, mystical experiences, or scriptures. Whether God is personal or not is also an exciting topic of discussion, including the question of God's gender, which is discussed in this article. The method used in this research is philosophical hermeneutics. The results of this study are 1) God's gender in the Hindu concept of divinity in the theological aspect of Nirguna Brahman is genderless, while in Saguna Brahman theology, God is manifested in masculine and feminine aspects, 2) Buddha has a genderless concept of God, but Mahayana sects also believe in Bhodisattvas who are respected and worshipped like one of them is Dewi Kwan Im, 3) Christians have a masculine concept of divinity as God, Elohim and the concept of the Trinity (God the Father/ Allah Bapa, God the Son/ Allah Putra and the Holy Spirit/ Roh Kudus). 4) Islam has a genderless concept of divinity, but in language it is categorized as masculine (he), 5) Confucianism believes in a transcendent God and believes in the power of Yin (female power) and Yang (male power).